Against the mafia: the classic Italian writings - Dalla Chiesa, Nando; Jerne, Christina (Palgrave Macmillan, 2024)
This collection of classic texts offers a longitudinal overview of the Italian mafia through the eyes of those who have questioned it in the past 144 years. It presents English translations of the key works of, among others, judges (Giovanni Falcone), political theorists (Gaetano Mosca), trade unionists (Pio La Torre), journalists (Giuseppe Fava), generals (Carlo Alberto Dalla Chiesa), and priests (Don Diana). These critical voices have been foundational to shaping the way Italian culture, policies and legislation relate to the mafia phenomenon. They represent different political standpoints, from elitism to communism, as well as vastly different times, from post-feudalism to hyper globalization. This book offers a rare (and hitherto untranslated) insight into, not only the history of the Italian mafia and its conceptualizations, but also into the movement against the mafia, which is one of the longest lasting (and most unrecognized) European social movements. It provides a useful historical archive of Italian political and sociological thought and a diversity of perspectives through which to tackle a complex and increasingly global criminological issue, making it relevant for those interested in Italian studies, political theory, sociology, criminology, legal studies, and history. Nando dalla Chiesa is Professor of Sociology of Organised Crime at the University of Milan, Italy. He has published numerous articles, books, and essays dedicated to understanding the mafia phenomenon from different angles. He is also a politician and the honorary president of Italy´s largest anti-mafia organisation, Libera. Christina Jerne is Assistant Professor at the Centre for Global Criminology at the University of Copenhagen, Denmark. She has published several articles on the topics of criminal enterprise, economic diversity and social movements. She is a member of the Community Economies Institute.